Attitudes of Employees Towards the Use of Social Media in Governmental Agencies in Saudi Arabia - Al-Ali, Fahad Moaqual (Journal of Economic, Administrative and Legal Sciences, 2020)
The study investigated the attitudes of employees in Saudi governmental agencies towards the use of social media means in the workplace. The study seeks to answer the following key question: "What are the attitudes of employees towards the use of social media in the workplace from the point of view of employees in government agencies in Saudi Arabia?" The importance of this study stems from the fact that the use of social media has become a reality in the workplace. Moreover, the importance of the study comes from the lack of studies in the field of subject, and the study sought to test a number of hypotheses, the most important of which is to know the statistical differences in the attitudes of workers towards the use of social media according to the quality and number of programs used most among workers during official working hours as well as the reasons for the use of social media.Samples were collected, which consisted of (416) employees from various governmental agencies. The researcher designed a questionnaire to collect information, which included (personal and functional characteristics, social media in the workplace). These were distributed to the sample of the study, namely the employees who attended training programs at the Institute of Public Administration in Riyadh, during the first two weeks of May 2018. The study found that WhatsApp was the most widely used among employees, followed by Twitter, YouTube and Snapchat. The communication for work was less than communication with family and friends as well as fun and entertainment. The percentage of employees using social media in the mornings and afternoons was high, The use of different social media in the workplace on a regular basis, as well as the reasons for the use of social media in general, varied between seeking new friendships, browsing entertainment sites, social networking, as well as the search for information for the purposes of work or communication for business purposes. The study recommended the value of educating employees both on the importance of employing social media for the benefit of work, and on the regulations and legislations for the optimal use of social media.